On the advantages of word frequency and contextual diversity measures extracted from subtitles: The case of Portuguese - Soares, Ana Paula; Machado, João; Costa, Ana; Iriarte, Álvaro; Simões, Alberto; de Almeida, José João; Comesaña, Montserrat; Perea, Manuel (Quarterly journal of experimental psychology (2006), 2015)
We examined the potential advantage of the lexical databases using subtitles and present SUBTLEX-PT, a new lexical database for 132,710 Portuguese words obtained from a 78 million corpus based on film and television series subtitles, offering word frequency and contextual diversity measures. Additionally we validated SUBTLEX-PT with a lexical decision study involving 1920 Portuguese words (and 1920 nonwords) with different lengths in letters (M = 6.89, SD = 2.10) and syllables (M = 2.99, SD = 0.94). Multiple regression analyses on latency and accuracy data were conducted to compare the proportion of variance explained by the Portuguese subtitle word frequency measures with that accounted by the recent written-word frequency database (Procura-PALavras; P-PAL; Soares, Iriarte, et al., 2014 ). As its international counterparts, SUBTLEX-PT explains approximately 15% more of the variance in the lexical decision performance of young adults than the P-PAL database. Moreover, in line with recent studies, contextual diversity accounted for approximately 2% more of the variance in participants' reading performance than the raw frequency counts obtained from subtitles. SUBTLEX-PT is freely available for research purposes (at http://p-pal.di.uminho.pt/about/databases ).